Peran pembelajaran Bahasa Indonesia di pendidikan tinggi dalam membangun critical thinking mahasiswa di era society 5.0 melalui debat ilmiah - Adelia Savitri (Universitas Tangerang Raya, 2023)
The development of Society 5.0 requires 4C abilities (communication, collaboration, critical thinking & problem-solving, creativity, and innovation) for students. This ability can be built through language skills and achievements in learning Indonesian. This research aims to reveal how Indonesian language learning plans in higher education make critical thinking & problem-solving in students through scientific debate. This research uses descriptive qualitative methods with Design-based Research (DBR). The results of this research show that the design of learning language skills through scientific debate, students can practice the four language skills: reading skill, speaking, listening, and writing. Apart from that, with scientific debates, students must think critically, find solutions to the cases raised in the debate, collaborate with teams to build arguments and practice communicating their arguments for the cases being discussed. Thus, learning Indonesian through scientific debate design is important in developing students' critical thinking skills in the Society 5.0 era.